2014
DOI: 10.9778/cmajo.20130064
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk among South Asians living in Canada: a systematic review and meta-analysis

Abstract: Background: South Asians represent about 3% of the Canadian population and have a higher burden of certain cardiovascular risk factors and cardiovascular disease (CVD) compared with white people. The objective of this study was to review the literature to compare cardiovascular risk factors and disease management practices among adult South Asian and white Canadians. Methods:We searched MEDLINE, Embase, Cochrane and Cumulative Index to Nursing and Allied Health Literature databases from their inception through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 59 publications
8
112
0
1
Order By: Relevance
“…In a meta-analysis of SA living in Canada, SA were approximately 60% less likely to smoke, 19 and lower smoking rates in SA have been found in the Netherlands and UK. 11,131,132 However, in a study in Ontario, Canada, longer duration of residence in Canada was associated with rise in CVD risk factors in SA, largely due to increases in smoking.…”
Section: Other Traditional Cvd Risk Factorsmentioning
confidence: 83%
See 3 more Smart Citations
“…In a meta-analysis of SA living in Canada, SA were approximately 60% less likely to smoke, 19 and lower smoking rates in SA have been found in the Netherlands and UK. 11,131,132 However, in a study in Ontario, Canada, longer duration of residence in Canada was associated with rise in CVD risk factors in SA, largely due to increases in smoking.…”
Section: Other Traditional Cvd Risk Factorsmentioning
confidence: 83%
“…With respect to traditional risk factors, a recent systematic review of SA in Canada showed that compared to other ethnic groups, SA had a greater prevalence of type 2 diabetes mellitus (DM), insulin resistance (IR), increased visceral adiposity, body fat, lower high density lipoprotein (HDL), increased carbohydrate intake and decreased physical activity. 19 DM was the most consistently elevated risk factor with a 1.4-2.5 fold increase in DM among SA compared to Europids. This may reflect the increased rates of abdominal obesity in SA compared to Europids.…”
Section: Ii) Etiologymentioning
confidence: 95%
See 2 more Smart Citations
“…South Asian individuals who live in Canada have been shown to have a greater burden of certain risk factors and subclinical disease but longer-term outcomes data are limited. 52 The role of socioeconomic status on risk of IHD and stroke among immigrants should also be further explored. Finally, the contribution of variance in cardiovascular risk factors to differences in cardiovascular risk should be evaluated, because few studies included in this review examined risk factor profiles.…”
Section: Future Studiesmentioning
confidence: 99%